VISUALIZATION OF SINUS NODE ARTERIES BY MULTISLICE SPIRAL COMPUTED TOMOGRAPHY CORONARY ANGIOGRAPHY - L. A. Bockeria; V. N. Makarenko; L. A. Yurpol’skaya; S. A. Alexandrova; M. A. Shlyappo (Вестник рентгенологии и радиологии)
Objective: to assess the capabilities of multislice spiral computed tomography coronary angiography (MSCT-CA) to visualize the anatomy of the sinus node artery (SNA). Material and methods. The retrospective analysis of coronary artery examinations covered 46 patients with the referral diagnosis of coronary heart disease. MSCT-CA showed no evidence of coronary artery stenosis. This sample included 23 (50%) men and 23 (50%) women; the mean age of the patients was 52.4±9.1 years; the mean height was 170±6.67 cm; the mean weight was 80.7±12.1 kg. X-ray computed tomography was carried out using a SOMATOM Definition AS+ 128-slice computed tomography scanner with retrospective ECG synchronization, reconstructed slice thicknesses of 1 and 3-mm. The Spearman correlation test was used for statistical data analysis. Results. The SNA was visualized in 83% of the patients. It originated from the right coronary artery (RCA) and the circumflex branch of the left coronary artery in 84 and 16% of cases, respectively. No significant association was found between the type of heart blood supply and that of sinus node one (r = 0.06). In 18% of cases, the SNA was visualized only at the level of the ostium, allowing the assessment of the origin of the artery, and at the level of its mid-third in 32%; the distal SNA bed was visualized up to its division; in 10% of them the artery could be visualized all the way, including the division (the dissipation site). Unclear visualization of the proximal SNA was observed among 17% of the patients in whom the SNA could not be visualized with a heart rate (HR) of more than 80 beats/min in 62.5% of the patients, less than 41 beats/min in 12.5%, and 60–61 beats/min in 25%. HR was not found to be associated with the quality of SNA visualization (r = 0.09). Conclusion. MSCT can assess the anatomy of SNA up to the distal bed and dissipation site. In the overwhelming majority of the patients, the SNA  originated from the RCA (84%) regardless of the type of heart blood supply. The best SNA visualization was noted with a HR of 50 to 80 beats per minute. There was no statistical relationship of the quality of visualization to HR.